The Journeys of a Taymiyyan Sufi : Sufism through the Eyes of ʿImād al-Dīn Aḥmad al-Wāsiṭī (d. 711/1311) - Post, Arjan (Studies on Sufism, 2020)
The Journeys of a Taymiyyan Sufi examines the life and doctrine of ʿImād al-Dīn Aḥmad al-Wāsiṭī (d. 711/1311), a little-known Ḥanbalī Sufi master from the circle of Ibn Taymiyya (d. 728/1328). The first part of this book follows al-Wāsiṭī's physical journey in search of spiritual guidance through a critical study of his autobiographical writings. This provides unique insights into several important manifestations of Sufism that he encountered as he travelled from Wāsiṭ to Baghdad, Alexandria, Cairo, and finally, Damascus. The second part focuses on his spiritual journey through a study of his Sufi writings, which convey a distinct type of Sufism that was specifically formulated within the boundaries of traditionalist theology as he understood it.